Du réservoir des Gallets à la piscine Saint-Georges - Isabelle Baguelin (In Situ)
The Gallets site, to the north of Rennes in the Ille-et-Vilaine department, conserves three underground reservoirs with masonry linings, dating from the 1880s, and a fourth reservoir in reinforced concrete dating from the beginning of the twentieth century. This infrastructural ensemble, with its associated aqueducts, was part of the city’s supply of drinking water, installed under the direction of the mayor of the time and the city’s architect, Jean-Baptiste Martenot. It was the first step in a policy of municipal hygiene that was pursued under the direction of the mayor Jean Janvier (1859-1923), in particular with the construction of the Saint-Georges swimming pool, between 1923 and 1926. This swimming pool was designed by the city’s architect Emmanuel Le Ray and is characteristic of the monumental hygienic architecture of the first half of the twentieth century. It boasts remarkable decoration by the Paris ceramics firm of Gentil & Bourdet and the Rennes mosaic artist, Odorico.